The benefits of early stimulation in neonates admitted to intensive care: A systematic review (Research, Society and Development, 2023)
Introduction: The incidence of premature births persists, causing adverse consequences for newborns. Physiotherapy plays an essential role in the early stimulation of neonates in the Neonatal Intensive Care Unit (NICU). Through specialized approaches and adapted techniques, physiotherapists work collaboratively to optimize the neuropsychomotor development of these fragile babies. Early intervention seeks to minimize potential sequelae, promote physical functionality, improve respiratory and postural adaptation, in addition to encouraging sensory interaction and emotional bonding with parents. Through an individualized approach, physical therapy in the NICU aims to improve the quality of life of these newborns, providing them with a solid foundation for healthy development and a successful transition to the out-of-hospital environment. Objective: To evaluate the effectiveness of early stimulation in newborns in the NICU, aiming for functional development and reduction of hospital stress, including analgesia and emotional bonds for stability of vital signs and early discharge. Methodology: A systematic review was carried out, collections were made from February to July 2023. Conclusion: Early stimulation in premature infants admitted to the NICU is essential to optimize the prognosis and quality of life of these premature infants.